Glycation Pattern of Captopril in Diabetics (Medical Forum Monthly, 2024)
Objective: Captopril is a chemical which acts as vasodilator and angiotensin- I converting enzyme inhibitor. The present attempt is to study the glycation inhibition pattern of captopril in diabetics and normals. Study Deign: Experimental Study. Place and Duration of Study: This study was conducted at the Research Lab., Department of Biochemistry, University of Agriculture, Faisalabad from May 2006 to February 2007. Materials and Methods: The study was designed on blood plasma from apparently healthy non-diabetic and diabetic persons. Plasma samples with different concentrations of glucose and that of captopril were prepared, followed by incubation for 5 weeks at 37 oC temperature. Glucose was estimated by glucose oxidase method before and after dialysis. Glycation level was measured by TBA and Periodate assays. Results: Increased glycation was observed from 1st to 3rd week of incubation while it decreased after 5th week due to the formation of advanced glycation end products. 10 mM concentration of captopril showed fairly good response to decrease glycation as compared to its other two concentrations. Conclusions: Highest concentration of captopril produced overall good enough of inhibition. Periodate borohydride appeared to be more reliable and sensitive glycation assay as compared to TBA.